The Evaluation Of The Implementation Of Preceptorship Model Training In Blud Rsud Nabire With Kirkpatrick Approach - Wibowo Hanafi Ari Susanto; Titih Huriah; Moh Afandi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Background: Preceptorship model is a continuous learning system that involves the role of nurses as role models and students in the clinical setting, the goal of preceptorship model learning is to form students to become professional nurses, having full sense of responsibility and knowledgeable, so that it will be able to improve the quality of nurses especially in the clinical setting as evidenced by accountability in the work, competence, therapeutic communications in the clinical setting. Preceptorship training is an activity to improve preceptor knowledge about nursing science development so that it can be implemented on the practice ground or guidance process. The effectiveness of a training program can be evaluated on the training process. Evaluating the training program is the last stage in the training itself. Kirkpatrick divides four levels in evaluating the process. There are reaction, learning, behavior and result of training.Objective: To analyze the evaluation of the implementation of the preceptorship model training at the BLUD RSUD Nabire with a Kirkpatrick approach.Method: The research method used was a descriptive quantitative. The total sample size was 14 respondents with a total sampling technique. Respondents were given intervention in the form of training of preceptorship modelResult: The reaction level showed a high positive reaction to the training of 86,83%, Knowledge level showed improvement in third measurement with a good category of 100% and attitude showed a positive category of 100%, behavior level showed the implementation of learning in a good category of 71 , 4% and the result level showed the result of B+ of 50%Conclusion: There was an influence of the implementation of Preceptorship Model training on reaction, learning, behavior and result. It was expected that clinical learning method could be integrated into nursing education curriculum. Keywords: Precepthorship Model; Training; Kirkpatrick